Risk of fatal industrial accidents and death from other external causes among asphalt workers. Issue 1 (22nd December 2003) - Burstyn, I; Boffetta, P; Järvholm, B; Partanen, T; Svane, O; Langård, S; Kauppinen, T; Stücker, I; Shaham, J; Heederik, D; Ahrens, W; Bergdahl, I; et al.
Abstract : The hypothesis that asphalt workers are at increased risk of mortality from industrial accidents and other external causes was tested. Mortality rates for external and violent causes of death in a cohort of asphalt industry employees from seven European countries and Israel were compared to that of the general population. There was no evidence that mortality from external causes was increased among long term employees in asphalt application and mixing. There was an increased risk for mortality due to external causes among short term workers. However, none of the fatal accidents among short term workers appear to have occurred during employment in the studied asphalt companies. Overall, no evidence was found supporting the hypothesis that asphalt workers are at increased risk of fatal industrial or road accidents. Mortality from other external causes did not increase in this population as a whole, but increased risks among short term workers deserve further attention.